Vulvar mastocytosis: case report and review of the literature. - Flórez Peña, J.; Vargas, L.; Rodriguez-Lechtig, B.; Pinzón, K.; Perez, N.; Torres-Pradilla, M. (European Journal of Pediatric Dermatology, 2025)
The case of an 11-year-old girl with a history of recurrent pruritic swelling of the right vulvar lip, which progressed over 18 months, was reported. The diagnosis of mastocytosis was confirmed by immunohistochemical analysis, which showed positivity of the markers CD117 and CD68 in the cells. To date, only twelve cases of vulvar mastocytosis have been reported, which predominantly involved the labia majora. The mean age at diagnosis is 10.5 years, with a significant delay between the onset of symptoms and diagnosis, underlining the importance of suspecting mastocytosis in the presence of vulvar nodules.